Examining the Portrayal of Indian women’s status via personal and political autonomy in Arundhati Roy’s selected novels - Suleman, Danish (2021)
In Indian society, women are facing a number of problems and challenges imposed by the so-called patriarchal society. They face personal and political issues simultaneously at different levels of their lives like household, marriage, jobs, education and health care. One can find several studies and books on women but there is no specific study conducted so far that focuses mainly on the personal and political autonomy issues of women in Indian society. Furthermore, the literature also lacks the use of a liberal feminist theory in order to highlight these issues. In order to fill these gaps, the researcher endeavoured to achieve the set objectives for the study which were to (a) examine the factors responsible for the sufferings of Indian women in Arundhati Roy’s two selected novels, i.e. The God of Small Things (1997) and The Ministry of Utmost Happiness (2017) and, (b) examine the evolution in the roles and status of women in Arundhati Roy’s second novel The Ministry of Utmost Happiness (2017) in personal and political autonomy aspects. In order to achieve these objectives, the Liberal feminist theory was used as a theoretical framework that helped the researcher to analyse the personal and political aspects of the novels. Qualitative content analysis was used to analyse these literary texts. The overall findings of this study reveal that (a) women issues and challenges in India were caused by violence, oppression, patriarchal society and identity crises, (b) personal and political autonomy did not serve these women in prospering their lives and providing their rights in the society, (c) women’s rights and identities were crushed by the powerful patriarchal members of the society who could not see women standing equal to them and (d) within a gap of two decades between the two selected novels, there was no considerable change or evolution that came in the situations of women as portrayed by Arundhati Roy. Furthermore, this research suggests that upcoming scholars should extend their literary studies by involving other novels from this two-decade gap (1997-2017) to compare as well as highlight the issues of women as portrayed by the authors of this period. This study also suggests that there is a need to have separate research on the oppressors and what makes them act violently towards women.